2012
DOI: 10.1111/j.1751-9020.2011.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Identity in Online Contexts: New Directives in the Study of a Classic Concept

Abstract: This article provides an overview of emerging research into the concept of deviant identity by highlighting major new directions in cyber‐deviance scholarship. We suggest that the examination of deviance in online settings offers unique new insights into the processes of identity construction and reinforcement, role play, and the social organization of deviant communities. We conclude by considering developments that may advance the literature on deviant identity in real world spaces, as well as expand the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…For individuals engaged in deviant lifestyles, the Internet is thus a tool to be harnessed, and there is a suggested, causal link between realized or desired deviance in real life and Internet adoption and use. The same can be said for a number of different online resources, including websites and message boards (Maratea and Kavanaugh, 2012). Stack et al (2004), for instance, showed that lifestyle elements such as communal ties and extramarital affairs predicted greater likelihoods of Internet pornography consumption.…”
Section: Criminal Lifestyles and Technological Adoptionmentioning
confidence: 78%
See 1 more Smart Citation
“…For individuals engaged in deviant lifestyles, the Internet is thus a tool to be harnessed, and there is a suggested, causal link between realized or desired deviance in real life and Internet adoption and use. The same can be said for a number of different online resources, including websites and message boards (Maratea and Kavanaugh, 2012). Stack et al (2004), for instance, showed that lifestyle elements such as communal ties and extramarital affairs predicted greater likelihoods of Internet pornography consumption.…”
Section: Criminal Lifestyles and Technological Adoptionmentioning
confidence: 78%
“…Studies of deviant subcultures online suggest that individuals turn to the Internet, motivated by desires to connect with others away from friends and family (Maratea and Kavanaugh, 2012; see also Jewkes and Sharp, 2003;Trautner and Collett, 2010;Wood and Ward, 2010). For individuals engaged in deviant lifestyles, the Internet is thus a tool to be harnessed, and there is a suggested, causal link between realized or desired deviance in real life and Internet adoption and use.…”
Section: Criminal Lifestyles and Technological Adoptionmentioning
confidence: 96%
“…Such safe spaces may simultaneously serve as social “insulation” (Sandstrom ) that deflects stigmatization and as a hindrance to full immersion with the “normals” (Goffman ). In a () review of studies of deviance in online communities, Maratea and Kavanaugh characterize these as “sanctuaries, or safe‐zones” (105) and note that participants “typically attempt to avoid sustained negative or abusive interactions with fellow members” (107). On the other hand, a great deal of research suggests that the identity of “gamer” and the identity of “female” pose problematic and sometimes dangerous dilemmas for those who would claim both (Fox and Tang ; Salter and Blodgett ; Wofford ).…”
Section: Walking a “Tightrope”mentioning
confidence: 99%
“…This is largely due to the convenient opportunities to obtain immediate information, develop and sustain criminal networks, maintain anonymity, operate with no borders, and limited regulation (Holt 2007 ;Maratea and Kavanaugh 2012 ;Pyrooz et al 2015 ;Weimann 2004 ). As a consequence, cybercrime has become a rapidly expanding global phenomenon (Interpol 2014 ).…”
Section: Introductionmentioning
confidence: 99%